2009
DOI: 10.1161/atvbaha.109.187997
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Cell Surface F 1 -ATPase Activity by Apolipoprotein A-I Inhibits Endothelial Cell Apoptosis and Promotes Proliferation

Abstract: Objectives— Several findings argue for a protective effect of high-density lipoproteins (HDLs) against endothelial dysfunction. The molecular mechanisms underlying this protective effect are not fully understood, although recent works suggest that the actions of HDL on the endothelium are initiated by multiple interactions between HDLs (lipid or protein moiety) and cell surface receptors. We previously showed that the mitochondrial related F 1 -ATPase is a cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
92
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(100 citation statements)
references
References 30 publications
7
92
0
1
Order By: Relevance
“…In mammalian cells, F1β is found mainly in mitochondria (13) but also at the plasma membrane (especially lipid rafts) (14)(15)(16). We confirmed these findings by carrying out immunofluorescence microscopy and a cell-fractionation assay ( Fig.…”
Section: F1βsupporting
confidence: 76%
“…In mammalian cells, F1β is found mainly in mitochondria (13) but also at the plasma membrane (especially lipid rafts) (14)(15)(16). We confirmed these findings by carrying out immunofluorescence microscopy and a cell-fractionation assay ( Fig.…”
Section: F1βsupporting
confidence: 76%
“…A recent population-based study has demonstrated that low IGF-1 was associated with impaired endothelial function in males [29]. On the other hand, different studies have established that HDL promotes endothelial cell proliferation and survival, and nitric oxide biosynthesis [23,30]. Thus, we may hypothesize that IGF-1 and HDL cooperate to favour endothelial integrity and repair.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, levels of the apoptosis-inducing protein truncated Bid are reduced in endothelial cells cultured in the presence of HDLs, whereas endothelial expression of the antiapoptotic protein Bcl-xL is enhanced (Riwanto et al 2013). The capacity of HDLs to attenuate apoptosis in endothelial cells requires induction of phosphatidylinositol 3-kinase (PI3K)/Akt/endothelial nitric oxide synthase (eNOS) signaling (Nofer et al 2001b;Riwanto et al 2013) and was attributed to apoA-I (Radojkovic et al 2009) as well as HDL-associated lysophospholipids (Kimura et al 2001;Nofer et al 2001b). More recently, a lower clusterin (or apoJ) and increased apoC-III content in the HDLs of patients with stable coronary artery disease or acute coronary syndrome was found to be associated with reduced antiapoptotic activities in human endothelial cells (Riwanto et al 2013).…”
Section: Preservation Of Endothelial Integritymentioning
confidence: 99%